Grass 2 cash @scale: Refined project theory of change - Sibiko, Kenneth W; Burkart, Stefan; Notenbaert, An (2023)
Vulnerable and market-oriented dairy farmers increase their livestock productivity through increased use of improved forages in the basal diet of their animals, leading to higher incomes, better nutrition and reduced environmental degradation